2011
DOI: 10.4103/1658-354x.84111
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose sequential combined-spinal epidural anesthesia for Cesarean section in patient with uncorrected tetrology of Fallot

Abstract: Tetrology of Fallot (TOF) is the most commonly encountered congenital cardiac lesion in pregnancy. Although there are controversies regarding safe anesthetic technique for parturient with TOF, we use low-dose sequential combined-spinal epidural anesthesia in such a case posted for Cesarean section and found that low dose (0.5 ml of 0.5%) intrathecal bupivacaine and fentanyl with sequential epidural bupivacaine supplementation was adequate for the performance of an uncomplicated Cesarean section with minimal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…In this case, where regional anaesthesia was not successfully placed, general anaesthesia was implemented. General anaesthesia is associated with several challenges in these patients; many of the agents used for induction and maintenance of general anaesthesia decreases the SVR with a potential of causing more right-to-left shunting through the VSD and there is risk of adverse haemodynamic responses associated with laryngoscopy and intubation that may lead to decompensation in these patients with reduced cardiac reserve 18. Phenylephrine was used as vasopressor in this case in anticipation of the drop in SVR caused by general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, where regional anaesthesia was not successfully placed, general anaesthesia was implemented. General anaesthesia is associated with several challenges in these patients; many of the agents used for induction and maintenance of general anaesthesia decreases the SVR with a potential of causing more right-to-left shunting through the VSD and there is risk of adverse haemodynamic responses associated with laryngoscopy and intubation that may lead to decompensation in these patients with reduced cardiac reserve 18. Phenylephrine was used as vasopressor in this case in anticipation of the drop in SVR caused by general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…When anesthetizing patients with congenital heart disease, under either a regional technique or general anesthesia, the following factors must be kept in mind; prevention of accidental intravenous infusion of air bubbles by using loss of resistance to saline rather than air to identify the epidural space, 9 a slow onset of epidural analgesia is useful, as rapid fall in SVR could result in reversal of shunt. [14][15][16] Supplemental O2 should be given to the patient throughout the procedure if regional technique is used. It is advisable to monitor O2 saturation as mild hypoxaemia may result in an increase in PVR and reversal of shunt flow.…”
Section: Discussionmentioning
confidence: 99%
“…There are case reports indicating the successful use of epidural, combined spinal epidural and continuous spinal anaesthesia in pregnant women with serious cardiovascular disease (7,9,10). It was reported that epidural anaesthesia effectively decreases birth-associated cardiac output increase and vascular wall tension (6).…”
Section: Discussionmentioning
confidence: 99%
“…Solanki et al (10) in a pregnant woman with cardiovascular risk, performed combined spinal epidural anaesthesia for caesarean section using 0.5 mL 0.5% hyperbaric bupivacaine and 25 μg fentanyl. As the level of sensory block remained at T10, an additional dose of 3 mL and 2 mL of 0.5% bupivacaine and 100 μg fentanyl was infused from the epidural catheter intermittently; they reported that the patient's hemodynamic status, who was given prophylactic phenylephrine infusion, remained stable.…”
Section: Discussionmentioning
confidence: 99%